Child Neglect - Sudiyanto Sudiyanto (Paediatrica Indonesiana, 1995)
Child neglect refers to failure to provide children's fundamental needs. In contrast to child abuse, which implies active negative conduct, child neglect means something passive. Child neglect may take a variety of forms including medical, physical, safety, sexual, educational, and emotional neglects. The neglects may manifest themselves as conditions reflecting the improper provision of child's needs. It should always borne in mind that child neglect is almost invariably resulted from complex process which has been influenced by family history, individual characteristics of the parents and children, social and environmental circumstances, and medical problems. Its management, therefore, should be thoroughly administered, and should involve many aspects and all parties in a team effort. The prevention of child neglect should include formal and informal education of the rights of the child.